Development of a multimedia interactive environment for PCBA simulation - Kok, Choon Seng. (2009)
This project consists of two modules to be considered and implemented. The first module involves a simulation study of the PCBA manufacturing line. The simulation study is to address a complete simulation project which includes the analysis of input data, model building, animation, analysis of model output statistics. The pair t-test statistical approach has been employed to validate the model. For first module, a PCBA manufacturing simulation model is built using MAST and the accuracy of the model validated against a similar model built using ProModel.